The potential of Muslim Friendly Hospitality in the tourism industry in Central Java - Iskandar Iskandar; Waridin Waridin; Deden Dinar Iskandar (Indonesian Journal of Islam and Muslim Societies, 2023)
This study aims to identify Muslim hospitality potential in the Central Java tourism industry. This research uses a hybrid research method or a Multiphase Mixed Method. Multiphase data were collected simultaneously between qualitative and quantitative data. Data were taken from literature studies, field observations, and in-depth interviews with key informants. The analytical methods used in this study included the Mic-Mac and Mactor analytical instruments, descriptive statistics, and Triangulation Methods. Results of the study show that although Central Java has not applied MFH regulations, the halal tourism industry is practiced in tourism. Central Java has all the potential for Muslim Hospitality with a score of 3.8 out of 5 based on the Indonesian Muslim Travel Index (IMTI) category. The potential for various scenic destinations, polite manner of community, stable and safe political conditions, financial institutions’ support, the existence of Islamic boarding schools, and both tangible and intangible Islamic historical heritage are all the strengths of MFH in Central Java. The theoretical implication of this research can be used as a starting point for further research. Whereas the applied implication suggests that the government needs a seed to immediately formulate regulations on Halal Tourism as affirmed by the state.